Diagnose Anthropologique A Partir Des Caractéristiques Dento-Squelettiques Et D’épaisseurs Des Tissus Mous Du Profil Facial: Etude Comparative Entre Population Autochtone Et Diaspora Etrangère - Ar, Assi; Jb, Beugre.; Jj, Gnadoh; Al, Beugre-Kouassi (European Scientific Journal, ESJ, 2016)
Objective : The aim of this study was to search for the particularities in the dento-skeletal and soft tissue thickness of the facial cutaneous profile of Black Ivorians and White Lebanese. Material and methods: This cross-sectional and descriptive study, concerned with numerical radiographs extracted from medical files of 119 adolescent patients [62 Ivorians (34 females and 28 males) and 57 Lebanese (31 females and 26 males)], from 11 to 16 years old, with skeletal class I and normodivergent faces, in first orthodontic surgery. From a drawing on acetate paper (Kodatrace type) and the materialization of true vertical and true horizontal (TVL and THL), 30 landmarks (19 cephalometric and 11 facial cutaneous profile landmarks) allowed the construction of lines and plans as well as 17 dento-skeletal measurements (10 angular et 7 linear) and 12 soft tissue thickness measurements. The data reliability was verified by Dahlberg’s error method, while the t of student on independent series (signification threshold at 0,05) allowed to compare dento-skeletal characteristics and soft tissue thickness of the two groups. The Results : Compared to White Lebanese, Black Ivorians present a facial prognathism resulting in more pronounced protrusion of alveolar bases (SNA= 85,714°, SNB= 81,321°, A-NPerp= 5,768°) and vestibuloversion of central incisives (I/i= 111,679°, I/NA= 7,214mm, i/NB= 9,036mm, NA and NB (I/NA= 27,952° and i/NB= 36,266°) responsible of the obtuser facial convexity (NA-Pog= 169,338°). Indeed, this facial convexity reveals a very low prominence of the chin (Pog-NB= -0,565 mm). Also, the maxillomandibular discrepancy observed (FMA= 24,516°, greater), implies a more important facial growth kinetic in vertical direction with black Ivoirians. This is considerably reduced with females, with a less pronounced FMA angle compared to Lebanese females [FMA° (P=0,211 ns)]. The cutaneous effect of that dento-skeletal prognathism, is tangible through more protrusive lips – hence, thicker - lips (Id-Ls= 13,677 mm and id-Li= 15,919 mm). In this way, the observed substantial thickness is justified, of supporting peri-buccal soft tissue [lower lip’s base (B-Sm= 13,742 mm) and the most inferior part of the chin (Me-Me’= 7,984 mm)]. The two males groups present, however, a soft tissue thickness relatively similar on all the chin surface [Pog-Pog’ (P= 0,393 ns); Gn-Gn’ (P=0,251 ns); Me-Me’ (P=0,245 ns)]. The Black Ivorians’ nose, platyrrhines, low and diving, present a thicker back (Rhi-Rhi’= 3,741 mm) and thin supporting peripheral soft tissue thickness (ENA-Prn = 22,468 mm, Prn perp/Sn-N’=12,935 mm, A-Sn= 13,097 mm) in general. In addition to those specific characteristics of Black Ivorians, males have a thicker soft tissue on the root of the nose (N-N’= 6,769 mm). Among the two female groups, the characteristics of soft tissue thickness are much more contrasted. Thus, besides the traditional morphological features (nose more prominent - so, thicker - with Lebanese females, and thicker lips with Ivorian females), the forehead (G-G’= 6,441mm) and the chin (Pog-Pog’= 13,941mm, GnGn’= 10,471mm, Me-Me’= 8,618mm) of Ivorian females are thicker. Conclusion : The characteristics of dento-skeletal and soft tissue thickness of Black Ivorians and White Lebanese, reflect the anthropological diagnosis of their original ethnical groups. Facial prognathism and acuteness of facial convexity are observed, as well as greater soft tissue thickness of the inferior facial third (especially in females) traditionally particularizing the negroAfricans. However, a morphological proximity of the two ethnic groups is noticeable among males, concerning the soft tissue thickness of the chin, but also in females as for facial divergence. This study, because of what the results highlightened, has a forensic anthropology interest, and reveals the importance of radiological cephalometry.